O sistema nacional de mobilidade urbana: do direito de acessar a cidade - Feltran, Fernanda Rodrigues (2017)
The present survey has as a theoretical framework the Urban Law and intends to be a multidisciplinary study between the areas of Law, Sociology and Urbanism, with the aim of investigating the National system of urban Mobility, limited of the urban highway system (excluding water and airway issues), as an instrument to enable the right of access to the city, under the aegis of the Right to the City. To this end, the fulfilment of the objective in a satisfactory way, the study deeply analyzes the meaning of the city and its social functions, reflecting its use and appropriation, equality and social inclusion, as well as sustainable urban development, of the National System of Urban Mobility with the legal bases of Law 12,587 of January 12, 2012, Urban Mobility Law. Direct result of the analysis allowed to identify the social externalities arising from the administrative management of the National System of Urban Mobility and the role of the State in its effectiveness, a scope of great importance in the context of large cities